Dealing with patients in healthcare: A self-assessment tool. Issue 6 (June 2016) - Gremigni, Paola; Casu, Giulia; Sommaruga, Marinella
Highlights: We developed the PPRQ to measure providers' relational competences with patients. The PPRQ is a 16-item self-evaluation tool that produced valid and reliable scores. The PPRQ may be used in day-to-day practice and within continuing education. Abstract: Objective: This study aimed to investigate how healthcare personnel self-evaluate their ability to relate to patients in day-to-day practice from a patient-centered perspective, and to test the psychometric properties of a questionnaire developed to assess it. Methods: A sample of 600 healthcare personnel, recruited among eight hospitals in various parts of Italy, completed the 16-item Provider-Patient Relationship Questionnaire (PPRQ). A sample of 50 nurses answered the PPRQ twice, at a four-week interval. The PPRQ validity, reliability and susceptibility to social desirability were tested. Results: PPRQ showed good reliability and structural validity, with four first-order factors: effective communication, interest in the patient's agenda, empathy, and patient involvement in care. Correlation with social desirability was negligible. Participants rated themselves as highly competent in communicating with patients, but less interested in involving the patient in care and in the patient's agenda. Differences in PPRQ dimensions were found between groups based on job type and geographic area. Conclusion: PPRQ is a brief self-report measure of the provider-patient relationship with promising psychometric properties in this sample. Practice implications: PPRQ has potential value in promoting a self-reflecting learning environment, whether through training or day-to-day practice.